Walter Benjamin and the Actuality of Critique Essays on Violence and Experience. - Salzani, Carlo (Cambridge Scholars Publisher, 2021)
The striking actuality of Walter Benjamin's work does not rest on a supposed ""usefulness"" of his philosophy for current concerns, but rather on the high ""legibility"" to which his oeuvre has come in the present. Indeed, this legibility is a function of critique, which unearths the truth-content of a work in a constellation of reading with the present, and assures thereby that the work lives on. Following this methodological tenet, this book approaches Benjamin's work with two foci: the actuality of his critique of violence, a central and unavoidable topic in the contemporary political-philo.